The instrumentation of public subsidies for private schools: Different regulatory models with concurrent equity implications. (January 2022) - Zancajo, Adrián; Verger, Antoni; Fontdevila, Clara
The availability of public funding for private schools, in both primary and secondary education, has become a common feature in a number of OECD countries. The expansion of public subsidies for privately owned schools has consequences that go far beyond the involvement of private actors in the provision of education. These include deepening forms of regulatory governance in educational systems and the blurring of frontiers between public and private education. Public subsidies for privately owned schools have been adopted following diverse rationalities and in pursuit of different goals. In light of the diversity, this research examines the regulatory configurations of private subsidized education provision across OECD countries, from a policy instruments' perspective. Based on a systematic review of the literature, the article identifies four models of regulation of private subsidized education, and analyses why and how these models have been problematized and have evolved accordingly. The paper pays particular attention to recent educational reforms adopted, in most cases, to tackle the equity challenges posed by publicly subsidized private provision. Finally, the paper elaborates on the implications that this form of provision has for public education and the achievement of equity goals, and reflects on the potential and limits of regulatory reforms when confronting these issues.